214k views
0 votes
What is (2x – 2)(x – 1)

User KimKha
by
5.8k points

2 Answers

6 votes
Hello!

First you multiply the 2x by the (x - 1)

2x * x = 2x^2
2x * -1 = -2x

Next you multiply the -2 by the (x - 1)

-2 * x = -2x
-2 * -1 = 2

Put the values together

2x^2 - 2x - 2x + 2

Combine like terms

2x^2 - 4x + 2

The answer is 2x^2 - 4x + 2

Hope this helps!
User Tsume
by
6.2k points
0 votes
Hello there!



Let's use foil.


First: 2x * x = 2x^2


Outside: 2x * -1 = -2x


Inside: -2 * x = -2x


Last: -2 * -1 = 2



Now, let's combine these.


2x^2 - 2x - 2x + 2


Finally, we can simplify this


-2x - 2x = -4x


2x^2 - 4x + 2




I hope I helped!


Let me know if you need anything else!


~ Zoe
User Mushahid Khatri
by
5.2k points